Vulnerability of the elderly: a conceptual analysis - Keylla Talitha Fernandes Barbosa; Fabiana Maria Rodrigues Lopes de Oliveira; Maria das Graças Melo Fernandes
ABSTRACT Objective: To analyze the concept of vulnerability of the elderly. Method: A concept analysis, according to the method proposed by Walker and Avant, operationalized through integrative review through search in scientific data portals using the Descriptors: Health vulnerability, aged, health services for the aged, health of the elderly, vulnerable populations and geriatric health services. To compose the literary corpus, 36 studies were selected. Results: Concept antecedents, as well as its attributes, were identified in individual, social and programmatic characteristics, which make up the characteristics of "vulnerability of the elderly", besides consequences of the phenomenon. These characteristics were analyzed with emphasis on aspects that contribute to the process of vulnerability of the elderly. Conclusion: The study demonstrated the multidimensionality of the phenomena studied, highlighting the peculiarities of vulnerability during aging. However, there is a need for further studies on the construct.